Spatio-temporal trends in zooplankton biomass in the northern Humboldt current system off Peru from 1961-2012. (November 2019) - Aronés, Katia; Grados, Daniel; Ayón, Patricia; Bertrand, Arnaud
Abstract: Anchovy ( Engraulis ringens ) is the most important exploited fish species in the Northern Humboldt Current System (NHCS) off Peru. This species, as well as most other pelagic resources, mainly forage on zooplankton. The NHCS is bottom-up controlled at a variety of scales. Therefore, fish biomass is driven by the abundance of their prey. In this context, we studied the spatiotemporal patterns of zooplankton biomass in the NHCS from 1961-2012. Data were collected with Hensen net all along the Peruvian coast. To transform zooplankton biovolume into biomass we used a regression that was calibrated from 145 zooplankton samples collected during four surveys and, for which, precise information was available on both biovolume and wet weight. The regression model was then applied on a time-series encompassing 158 cruises performed by the Peruvian Institute of the Sea (IMARPE) between 1961 and 2012. We observed a clear multidecadal pattern and two regime shifts, in 1973 and 1992. Maximum biomass occurred between 1961 and 1973 (61.5 g m −2 ). The lowest biomass (17.8 g m −2 ) occurred between 1974 and 1992. Finally, the biomass increased after 1993 (26.6 g m −2 ) but without reaching the levels observed before 1973. A seasonal pattern was observed with significantly more biomass in spring than in other seasons. Spatially, zooplankton biomass was higher offshore and in northern and southern Peru. Interestingly, the zooplankton sampling was performed using classic zooplankton net that are well fitted to mesozooplankton and are known to underestimate the macrozooplankton; however, the spatiotemporal patterns we observed are consistent with those of macrozooplankton, in particular euphausiids. This suggests that in the NHCS, when and where macrozooplankton dominates it also dominates the biomass obtained using classic zooplankton net samples. Finally, until now, in the NHCS only time-series on zooplankton biovolume were available. The biomass data we provide are more directly usable in trophic or end-to-end models.